The effect of strategic green marketing orientation on customer satisfaction: The mediating role of green corporate image - Alauddin, Md (IIUC Business Review, 2022)
Green marketing plays a significant role in promoting environment friendly products and developing a positive green image worldwide. This research aims to determine the role of green marketing orientation (GMO) on green corporate image (GCI) and green customer satisfaction (GCS). This research also examines the role of GCI as a mediator in the link between GMO and GCS. Data were collected from two hundred and fifteen clients of hotels in Hong Kong. The data were gathered using survey methods through the convenience sampling technique. The results indicate that green marketing orientation positively influences both green corporate image and green customer satisfaction. Furthermore, the findings demonstrate that GCI serves as a mediator between GMO and GCS. These findings suggest that hotel managers should develop a positive green image by designing the green marketing mix to enhance the level of green customer satisfaction. The research also brings out the significance of the GMO actions that are required for developing GCI and GCS. IIUC Business Review, Vol.-11, Issue-1, Dec. 2022, pp. 71-94